The Effect of Sheep Dung on the Growth of Odot Grass (Pennisetum purpureum cv. Mott) - Pratama, Said Mirza; Nasution, Siti Shofiya; Izzati, Raichan; Zikria, Virda (Jurnal Sain Peternakan Indonesia, 2023)
Forage plays a vital role because it contains substances needed by livestock that can be used for energy metabolism and to support reproduction. Odot grass is very potent and is one of the varieties of elephant grass that grows not too high so that it can be used as shepherd grass. This study aims to see the effect of sheep dung fertilizer application on plant height, number of leaves and leaf area of Odot grass. This study was an experimental trial designed based on a completely randomized design (RAL), with five treatments and four replications: P0 (without sheep dung), P1 (125 gr/hole), P2 (250 gr/hole), P3 (375 gr/hole), and P4 (500 gr/hole). The results showed that the number of sheep dung did not have a significant effect on all research parameters (height, leaves, and leaf area on Odot grass plants); this was most likely caused by the nutrient conditions of the soil where the research was still relatively extensive and met the needs for the growth of Odot grass, so it was not seen the effect of sheep dung on the growth phase of Odot grass (age 0-60 days).